Remote consultations in mental health: collaborative evaluation applying learning health systems thinking - Lucy Goulding; Julie Williams; Alison White; Aileen Jackson; Zoë Lelliott; Stuart Adams; Kia-Chong Chua; Noushig Nahabedian; Juliana Onwumere; James Woollard; MOMENT group AishaAbdullah StuartAdams CeciliaCasetta ChuaKia-Chong SarahCope NatashaCurran LydiaDavies LenDemetriou EmilyFinch PeterFonagy FionaGaughran McManusMelanie Getty LucyGoulding ElizabethGraham BarbaraGrey AileenJackson HarrietJordan RobertLawrence ZoeLelliott PaulLennon AlexLloyd SophieLowry SarahMarkham NoushigNahabedian JulianaOnwumere NinaPearson OwenJacqueline Phillips LanaSamuels NickSevdalis AndrewWalker AlisonWhite JulieWilliams GabriellaWojewodka JamesWoollard RebeccaAppleton MonikaBadhan PhoebeBarnett HaimeZoë Harju-SeppänenJasmine SoniaJohnson Lloyd-EvansBrynmor JipingMo JustinNeedle AlexandraPapamichail EmilyRoxburgh JuanNorha Vera San MerleSchlief SpyrosSpyridonidi RainsLuke Sheridan AlanSimpson ThomasSteare MagdalenaTomaskova WoodLisa; Nick Sevdalis; et al. (BJPsych Bulletin)
Aims and method A collaborative evaluation of remote consultations in mental health services was undertaken by mental health service providers, experts by experience, academic institutions and a Health Innovation Network in south London, UK. ‘Learning healthcare systems’ thinking was applied. Workstream 1 reviewed international published evidence; workstream 2 synthesised findings from three health provider surveys of the perceptions and experiences of staff, patients and carers; and workstream 3 comprised an electronic survey on local projects.